Sustainable light olefins synthesis via CO2 hydrogenation: Comparative exergetic, exergoeconomic, and exergoenvironmental analyses - Wang, Lei; Zhang, Leiyu; Gao, Ruxing; Zhang, Chundong; Jun, Ki Won; Kim, Seok Ki; Zhao, Tiansheng; Wan, Hui; Guan, Guofeng; Jing, Wenheng (Journal of Environmental Chemical Engineering, 2024)
CO2-to-olefins (CTO) technology has emerged as a worthy solution for green olefin production and greenhouse gas emissions mitigation. However, most of the present researches focus on the development of high-performance catalysts, while few of them devote to the process design and performance evaluation. Hence, this study proposed three candidate CTO processes via methanol-mediated, direct and indirect FTS-based routes. Based on the rigorous modeling and simulation, exergy-based (i.e., exergetic, exergoeconomic, and exergoenvironmental) analyses were conducted to quantify the overall exergy dissipation, economic cost, and environmental impacts. More specifically, we carefully assessed and compared their comprehensive performances from the system-level, and discern the origins and formation of economic cost and environmental impacts from the component level. As a result, the direct FTS-based process has the highest exergy efficiency of 68.65 %, while the indirect FTS-based process and the methanol-intermediated process exhibit the lowest unit exergoeconomic cost and exergoenvironmental impacts of 0.147 $/kW and 38.55 mPts/kW, respectively. In addition, some pertinent optimization suggestions were proposed to enhance the systems’ thermodynamic efficiency, economic and environmental benefits. Overall, this study offers crucial insights into the thermodynamic irreversibility, economic viability, and environmental sustainability of the proposed CTO systems, propelling the frontiers of future sustainable olefin production.
Keywords: CO2 hydrogenation; Economic costs; Exergetic; Exergoeconomics; Exergy-based analyse; Greenhouse gas emissions; Life cycle assessment; Light olefins synthesis; Light-olefins; Olefin production; CO2 hydrogenation; Exergy-based analysis; Life cycle assessment; Light olefin